PENGARUH PENERAPAN SISTEM INFORMASI E-SAMSAT TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Alghaviqi, Muhammad Wafqi Aufa; Ishak, Jouzar Farouq (Jurnal Riset Akuntansi, 2023)
This research was conducted to determine the influence of the implementation of the E-Samsat information system on motor vehicle taxpayer compliance at the SAMSAT Garut Regency office. The research method used is descriptive quantitative. The number of samples used in this study were 100 respondents with several criteria. Primary data obtained through a questionnaire. From the results of the coefficient of determination test, the application of the E-Samsat information system has an influence on the compliance level of motor vehicle taxpayers by 29.5%. As for the results of hypothesis testing, it can be seen that the tcount value is 6.407 and the ttable value is 1.984. These results indicate that the tcount value is greater than the ttable value so it can be concluded that H0 is rejected and H1 is accepted. Thus it can be concluded that there is a positive influence between the application of the E-Samsat information system on motor vehicle taxpayer compliance in Garut Regency. Keywords: E-Samsat, Vehicle Tax, Taxpayer Compliance